Development and validation of a food frequency questionnaire for consumption of polyphenol‐rich foods in pregnant women. Issue 4 (15th January 2013) - Vian, Izabele; Zielinsky, Paulo; Zilio, Ana Maria; Mello, Anne; Lazzeri, Bruna; Oliveira, Andressa; Lampert, Kenya Venusa; Piccoli, Antônio; Nicoloso, Luis Henrique; Bubols, Guilherme Borges; Garcia, Solange Cristina
Abstract Previous studies have shown that maternal consumption of polyphenol‐rich foods after the third trimester of pregnancy may interfere with the anatomical and functional activity of the fetal heart as, to our knowledge, there are no validated instruments to quantify total polyphenols in pregnant women. The aim of this study was evaluate the reproducibility and validity of a food frequency questionnaire (FFQ), with 52 items, to assess the intake of polyphenol‐rich foods in pregnant women in Brazil. This cross‐sectional study included 120 pregnant women who participated in nutritional interviews in two moments. The intake of polyphenols estimated by the developed FFQ was compared with the average of two 24‐h recalls (24HR), with the average intake measured by a 3‐day food diary (D3days) and with the urinary excretion of total polyphenols. The triangular method was applied to calculate Pearson's correlation coefficients, intraclass correlation and Bland–Altman plots for the FFQ, using an independent biochemical marker, in addition to classification by quarters of consumption. The questionnaires were log transformed, adjusted for body mass index and gestational age. The adjustment for energy was applied only of 24HR and D3days. Analysis of the reproducibility between the FFQ showed a very high correlation (r = 0.72; P < 0.05). A low but significant association was observed between the FFQ and urinary excretion (0.23; P = 0.01). The association between the dietary survey methods was moderate to very high (r = 0.36 to r = 0.72; P < 0.001). In conclusion, this questionnaire showed reproducibility and validity for the quantification of consumption of total polyphenols in pregnant women.